Filosofi Pendidikan Ekopedagogi dalam Pembelajaran Sastra: Membangun Kesadaran Lingkungan Mahasiswa Melalui Puisi Theoresia Rumthe - Wa Mirna (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2026)
This study aims to describe the values ​​of ecopedagogy education philosophy contained in the poems by Theoresia Rumthe in her book